Adab Dalam Belajar dan Pembelajaran Sebagai Landasan Pembentuk Karakter Peserta Didik - Hawra Hawra; Parsa Aulia Afifah; Siti Mayitoh (Journal Innovation In Education, 2025)
Manners in learning and learning are fundamental aspects in Islamic education that not only emphasize academic achievement, but also play a big role in the formation of students' character and morals. Ignoring the values of manners can give birth to an intelligent but less moral generation. This article aims to examine the urgency and implementation of adab in the learning and learning process. This study uses a qualitative approach with a literature study method. Data was collected from relevant scientific journals, textbooks, and academic articles, and then analyzed using content analysis techniques to prepare a conceptual synthesis of the meaning, role, and internalization of adab in education. The results of the study show that adab is a key element in creating a harmonious and effective learning atmosphere. Student manners include sincere intentions, tawadhu' attitudes, and respect for knowledge and teachers. Meanwhile, the manners of teachers reflect example, sincerity, and justice in educating. Civilized interaction between teachers and students strengthens the internalization of values and creates a conducive learning environment. The main challenges of cultivating adab in the modern era include the influence of digital culture and educational orientation that focuses on academic achievement alone. Therefore, adab must be the main foundation in education to form people who are knowledgeable and have noble character. Education that instills good manners consistently from an early age will produce a generation that is not only superior in knowledge, but also wise in action. This article presents a comprehensive conceptual approach to the integration of adab values into the entire modern educational process and emphasizes the importance of synergy between the roles of families, educational institutions, and society.